An Analysis of Students’ Anxiety in Speaking - Uli Modesta Siagian; Adam Adam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This thesis aims to define the factors of students’ speaking anxiety and how the students’ strategies to overcome speaking anxiety in the class room. The problem in this research is anxiety of tenth grade students SMK Indomalay School Batam to speak in classroom. Based on the issues above, the purpose of this researcher is to define the factor causing of speaking anxiety and how the students' strategies to overcome speaking anxiety. This research is qualitative descriptive. The subject in this study is tenth grade of SMK Indomalay School Batam in Academic year 2015/2016. The totally number is 22 students.  The data collected by Interview and questionnaire. The results showed that the factor causing of the students' speaking anxiety to speak in the language classroom are:  lack of familiarity of task, fear of making mistakes, low motivation, incomprehensible inputs, lack of confidence and then low English proficiency. And the student’s strategies to overcome speaking anxiety were peer seeking, preparation, relaxation, positive thinking and resignation. Keywords: students’ anxiety, speaking